Pregnancy outcomes in patients with chronic kidney disease：a Meta analysis - Yu-ye Li; Qing-nan Zhu; Yu Sun; Qing-si Wen; Yan Shi; Ze-wen Yan; Hong-li Lin; Da-peng Wang; Jun-jun He (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To systematically evaluate the impact of chronic kidney disease (CKD) on pregnancy outcomes in pregnant patients. Methods Computer searching was conducted within the databases of MEDLINE, EMBASE, WANFANG DATA, China National Knowledge Infrastructure (CNKI) and China Biomedical Literature Database (CBM) from the establishment to July 2023 to identify the relevant literature items on the impact of CKD on pregnancy outcomes in pregnant patients. Two researchers independently screened the literature, extracted data and evaluated the quality of the included studies. Meta-analysis was performed with Review Manager 5.3 and STATA 17.0 software. ResultsA total of 15 case-control and cohort studies, including 2,785,115 subjects, were included for final analysis. The results of Meta-analysis demonstrated the following adverse pregnancy outcomes: CKD elevated the risk of adverse pregnancy outcomes, including preeclampsia (OR=2.68, 95%CI:1.47-4.89), gestational hypertension (OR=6.29, 95%CI:2.58-15.32), preterm birth (OR=4.62, 95%CI:2.78-7.67), small for gestational age (OR=1.54, 95%CI:1.24-1.91) and low birth weight (OR=2.44, 95%CI:1.78-3.35). CKD stage 3-5 patients were more prone to severe preeclampsia (OR=2.31, 95%CI:1.35-3.94), preterm birth (OR=5.06, 95%CI:3.28-7.79), small for gestational age (OR=3.85, 95%CI:1.91-7.76), low birth weight (OR=2.90, 95%CI:1.37-6.13) and fetal mortality (OR=3.41, 95%CI:1.33-8.73) as compared with CKD stage 1-2 counterparts. Pregnant patients with massive proteinuria were more prone to severe preeclampsia (OR=2.76, 95%CI:1.89-4.04), gestational hypertension (OR=2.38, 95%CI:1.62-3.50), preterm birth (OR=3.84, 95%CI:2.69-5.47), low birth weight (OR=2.38, 95%CI:1.62-3.50) and fetal mortality (OR=2.45, 95%CI:1.44-4.17) as compared with those with mild proteinuria. Conclusion CKD elevates the risk of adverse pregnancy outcomes, including preeclampsia, gestational hypertension, preterm birth, small for gestational age and low birth weight. Pregnant patients with CKD stage 3-5 or massive proteinuria (≥1 g) are more prone to adverse pregnancy outcomes as compared with those with CKD stage 1-2 or mild proteinuria (<1 g).